2007
DOI: 10.1073/pnas.0611405104
|View full text |Cite|
|
Sign up to set email alerts
|

A common variant in combination with a nonsense mutation in a member of the thioredoxin family causes primary ciliary dyskinesia

Abstract: Thioredoxins belong to a large family of enzymatic proteins that function as general protein disulfide reductases, therefore participating in several cellular processes via redox-mediated reactions. So far, none of the 18 members of this family has been involved in human pathology. Here we identified TXNDC3 , which encodes a thioredoxin–nucleoside diphosphate kinase, as a gene implicated in primary ciliary dyskinesia (PCD), a genetic condition characterized by chronic respiratory tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(104 citation statements)
references
References 58 publications
0
101
0
2
Order By: Relevance
“…Reduced movement of ciliary beating causes primary ciliary dyskinesia, including Kartagener syndrome, characterized by situs inversus, bronchiectasis, and chronic sinusitis (40). Such dysmotility or immotility of the cilia results from genetic mutations of major components of the axonema such as dyneins (52)(53)(54), DNA polymerase (55), sperm-associated antigen 6 (56), and a thioredoxin family member (57). In this study, we demonstrated that HSF1 is required for maintenance of ciliary beating in various organs such as the nasal cavity, ventricles, trachea, and oviducts.…”
Section: Discussionmentioning
confidence: 76%
“…Reduced movement of ciliary beating causes primary ciliary dyskinesia, including Kartagener syndrome, characterized by situs inversus, bronchiectasis, and chronic sinusitis (40). Such dysmotility or immotility of the cilia results from genetic mutations of major components of the axonema such as dyneins (52)(53)(54), DNA polymerase (55), sperm-associated antigen 6 (56), and a thioredoxin family member (57). In this study, we demonstrated that HSF1 is required for maintenance of ciliary beating in various organs such as the nasal cavity, ventricles, trachea, and oviducts.…”
Section: Discussionmentioning
confidence: 76%
“…Two main genes, DNAI1 and DNAH5 have been identified to date [33,34] for PCD with isolated ODA defects and the other identified genes (i.e. RPGR, TXNDC3, DNAH1, DNAI2, KTU, RSPH9 and RSPH4A) concern a few PCD families [35][36][37][38][39][40]. The identification of the ciliary ultrastructural defect by TEM analysis could also be helpful for genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the genes identified (table 1) to date for autosomal recessive PCD variants (dynein, axonemal, intermediate chain 1 (DNAI1) and 2 (DNAI2) and heavy chain 5 (DNAH5) and 11 (DNAH11) and thioredoxin domain containing 3 (TXNDC3)) encode outer dynein arm (ODA) components [15][16][17][18][19][20], whereas only one gene (chromosome 14 open reading frame 104 (KTU)) is required for cytoplasmic preassembly of axonemal dyneins [21]. In addition mutations in the two genes, radial spoke head 9 homologue (RSPH9) and 4 homologue A (RSPH4A), have been reported in PCD patients with abnormalities of the central microtubular pair [22].…”
Section: Genetics and Inheritancementioning
confidence: 99%